THE EFFECTIVENESS OF JIGSAW LEARNING METHOD COMPARED TO LECTURE-BASED LEARNING IN ANATOMY LECTURES - Saharnauli J. Verawaty Simorangkir (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Jigsaw is a cooperative learning method in which students work together in small groups, helping one another towards a common goal. The aim of this research were to find out the different effect of Jigsaw cooperative learning method with conventional method in terms of anatomy learning achievement and retention. Method: Forty-nine students were randomly assigned into two groups, control group (n=24) and experimental group (n=25). A pretest was administered to all students before classes. The Jigsaw learning method was applied to the experimental group for one session. At the same day, control group was taking classes using the lecture-based learning method. At the end of session, all students were retested (post test) on subject. A retention test was administered 3 weeks after the post test. Mean scores were calculated for each test for the experimental and control groups, and the data obtained were analysed using the independent samples t-test.Results: No significant difference was determined between the Jigsaw and lecture based methods at pretest or post-test. The highest mean test score was observed in the post-test with the Jigsaw method. In the retention test, no significant difference between the Jigsaw and lecture-based methods. The highest mean retention test score was observed in the lecture-based method.Conclusion: The Jigsaw method is less effective than lecture-based method.